REKONSTRUKSI PEMBANGUNAN EKONOMI BERBASIS ISLAM Telaah Pemikiran M. Umer Chapra - Fadllan Fadllan (Research Institute and Community Engagement of IAIN MADURA, 2018)
The meaning of “Reconstruction of Economic Growth” in this research is an effort to reconceptualize the economic concepts of conventional development, structure and economic system formulated by West through the mind frame offerred by Muhammad Umer Chapra. This mind set has a purpose of reconstructuring the economic growth that can make the society prosperous as the Islamic teaching law, so that it can create a new theory as a future economic developmental concept. To build a fairness economic system and to reach the economic goals, M. Umer Chapra offerred a reconstruction on some strategic elements. They are filter mechanism which stressed on the moral filter, people’s motivation to put social interests forward, socioeconomical reconstruction, and the country complementer’s active role in economy. To make it true, he offerred some policies, they are: 1) enlighting the humanity factors; 2) decreasing the property concentration; 3) making the economic reconstruction; 4) making fund reconstruction; 5) making a strategic policy with the society’s welfare as the orientation. The essence of all his offering about economic growth is a balanced development in two sides, economy and moral. Because it is impossible to bulid a fairness welfare without any moral development.